Non-Rapid Eye Movement Sleep Parasomnias and Migraine: A Role of Orexinergic Projections - Messina, Antonietta; Bitetti, Ilaria; Precenzano, Francesco; Iacono, Diego; Messina, Giovanni; Roccella, Michele; Parisi, Lucia; Salerno, Margherita; Valenzano, Anna; Maltese, Agata; Salerno, Monica; Sessa, Francesco; et al. (Frontiers in Neurology, 2018)
Introduction: Sleep and migraine share a common pathophysiological substrate, although the underlying mechanisms are unknown. The serotonergic and orexinergic systems are both involved in the regulation of sleep/wake cycle and numerous studies show that both are involved in the migraine etiopathogenesis. These two systems are anatomically and functionally interconnected. Our hypothesis is that in migraine a dysfunction of orexinergic projections on the median raphe nuclei, interfering with serotonergic regulation, may cause NREM parasomnias, such as somnambulism. Hypothesis/Theory: Acting on the serotonergic neurons of the raphe nuclei, the dysfunction of orexinergic neurons would conduct to a higher release of serotonin. The activation of serotonergic receptors located on the walls of large cerebral vessels would lead to abnormal vasodilatation and consequently increasing of transmural pressure. This process could activate the trigeminal nerve terminals that innervate vascular walls. By consequence, there is activation of sensory nerve endings at the level of hard vessels in the meninges, with release of pro-inflammatory peptides (e.g. substance P and CGRP). Within this hypothetical frame, the released serotonin could also interact with trigemino-vascular afferents to activate and/or facilitate the release of the neuropeptide at the level of the trigeminal ganglion. The dysregulation of the physiological negative feedback of serotonin on the orexinergic neurons, in turn, would contribute to an alteration of the whole system, altering the sleep-wake cycle. Conclusion: Serotonergic neurons of the median raphe nuclei receive an excitatory input from hypothalamic orexin/hypocretin neurons and reciprocally inhibit orexin/hypocretin neurons through the serotonin 1A receptor (or 5-HT1A receptor). Considering this complex system, if there is an alteration it may facilitate the pathophysiologic mechanisms involved in the migraine, while it may produce at the same time an alteration of the sleep-wake rhythm, causing sleep disorders such as sleepwalking. Understanding the complex mechanisms underlying migraine and sleep disorders and how these mechanisms can interact with each other it would be crucial to pave the way for new therapeutic strategies.